Unilateral single-port thoracoscopic surgery for bilateral pneumothorax or pulmonary bullae - Xiaojian Li; Xiaojin Wang; Huayong Zhang; Hua Cheng; Qingdong Cao (Journal of Cardiothoracic Surgery, 2019)
Abstract Background Rapid rehabilitation surgery has become a widely accepted approach. Thoracic surgeons have attempted in many ways to make surgery less invasive. We combined tubeless technology, single-port technology and mediastinum approach for the treatment of simultaneous bilateral primary spontaneous pneumothorax(PSP)or pulmonary bullae. And we evaluated its therapeutic effect. This study aimed to investigate if tubeless single-port video-assisted thoracic surgery (Tubeless-SPVATS) via anterior mediastinum can be used as an alternative surgical treatment for bilateral lung diseases, especially for concurrent or contralateral recurrence PSP. Methods From November 2014 to December 2016, 18 patients with simultaneous bilateral PSP or pulmonary bullae were treated with tubeless -SPVATS via anterior mediastinum. They were 13 males and 5 females with an average age of 20.2 ± 2.3 years (17 to 24 years). They all had preoperative chest CT and were diagnosed with simultaneous bilateral PSP or pulmonary bullae. Results Fifteen patients underwent bilateral bullae resection with Tubeless-SPVATS via anterior mediastinum. Three patients underwent bilateral single-port video-assisted thoracic surgery. No thoracotomy was performed. No death and grade 3-4 mobidity were found. All the patients started eating 6 hours after surgery. The average operation time was 44.56±17.8min. The patients were discharged 3. 5±1.0 days postoperatively. Conclusions Tubeless-SPVATS via anterior mediastinum is a safe and feasible treatment for patients with simultaneous bilateral PSP or pulmonary bullae. However,contralateral thoracic is not explored fully enough. And when contralateral lung bullae are located near the hilum, endoscopic linear stapler cannot be easily used to conduct suture. Thus, the recurrence rate after performing Tubeless-SPVATS may be increased compared to performing thoracotomy. However, compared to bilateral thoracic surgery, this method reduced postoperative pain. And it took significantly less time than bilateral thoracic surgery. Thus, this method has some clinic value.